Functional responses and molecular mechanisms involved in histone-mediated platelet activation - Carestia, Agostina; Rivadeneyra, Leonardo; Romaniuk, Marìa Albertina; Fondevila, Carlos; Negrotto, Soledad; Schattner, Mirta (Thrombosis and Haemostasis, 2013)
Histones are highly alkaline proteins found in cell nuclei and they can be released by either dying or inflammatory cells. The recent observations that histones are major components of neutrophil extracellular traps and promote platelet aggregation and platelet-dependent thrombin generation have shown that these proteins are potent prothrombotic molecules. Because the mechanism(s) of platelet activation by histones are not completely understood, we explored the ability of individual recombinant human histones H1, H2A, H2B, H3 and H4 to induce platelet activation as well as the possible molecular mechanisms involved. All histones were substrates for platelet adhesion and spreading and triggered fibrinogen binding, aggregation, von Willebrand factor release, P-selectin and phosphatidylserine (PS) exposure and the formation of platelet-leukocyte aggregates; however, H4 was the most potent. Histone-mediated fibrinogen binding, P-selectin and PS exposure and the formation of mixed aggregates were potentiated by thrombin. Histones induced the activation of ERK, Akt, p38 and NFkB. Accordingly, histone-induced platelet activation was significantly impaired by pretreatment of platelets with inhibitors of ERK (U 0126), PI3K/Akt (Ly 294002), p38 (SB 203580) and NFkB (BAY 11–7082 and Ro 106–9920). Preincubation of platelets with either aspirin or dexamethasone markedly decreased fibrinogen binding and the adhesion mediated by histones without affecting P-selectin exposure. Functional platelet responses induced by H3 and H4, but not H1, H2A and H2B, were partially mediated through interaction with Toll-like receptors –2 and –4. Our data identify histones as important triggers of haemostatic and proinflammatory platelet responses, and only haemostatic responses are partially inhibited by anti-inflammatory drugs.
Keywords: Histones; platelets; neutrophil extracellular traps; inflammation